DNA migration through semi-circular gradient channel - Mohanta D. (My University, 2025)
We study quasi-equilibrium migration of double stranded DNA (dsDNA) through semi-circular narrow channel by exact enumeration method. We employ Fokker–Planck formalism to analyze the slow migration process of dsDNA through this symmetric channel which resembles the Herpes Simplex Virus -1 (HSV-1) migration through the vestibular nuclei in brainstem. We explore all possibilities of varying solvent gradient inside the semi circular area to ensure slow migration which is essential in DNA nanopore sequencing techniques. We also shed light on configurational and orientational properties of DNA and sequential preference of the dsDNA while migrating through the channel. We report that GC rich homo-sequence DNA migrates more slowly through the channel than AT rich and AT-GC di-block DNA. In this paper, a simple lattice model is developed to explore various physical parameters dependence on slow migration process of a dsDNA. © 2021 Elsevier B.V.